Total Cost of Ownership of Open Source - Fitriati Akmila (Universitas Islam Indonesia, 2008)
There has been a huge interest among academics and practitioners in open source. This is because open source offers business with its programmers the opportunity to elaborate and adapt source code. The success of open source leads to an increasing contro-versy of the price of its software. In other words, is the total cost of ownership of open source really lower than that of proprietary software?This paper describes the concept of open source, compares it with proprietary software, and total cost of ownership (TCO) of open source. An example of Linux vs. Windows or Unix is taken to describe the cost of open source. In brief, this paper sums up open source is cheaper in terms of direct cost (hard-ware, software and support). However, it is difficult to measure the indirect costs of open source since these costs are hidden and may vary within the business and software environment.Keywords: Open Source; Proprietary Software; Total Cost of Ownership